Sacral Neuromodulation Treatment for Non-neurogenic Urological Disorders: Experience of a Single Center in Turkey - Adem Emrah Coğuplugil; Sercan Yılmaz; Bahadır Topuz; Murat Zor; Engin Kaya; Mesut Gürdal (Journal of Urological Surgery)

(untitled)
Objective:We evaluated the success rate and complications of sacral neuromodulation (SNM) in patients with non-neurogenic urological disorders.Materials and Methods:We retrospectively evaluated patients with an overactive bladder (OAB), bladder pain syndrome/interstitial cystitis (BPS/IC), and idiopathic non-obstructive urinary retention (IUR), who underwent SNM between 2015 and 2020. SNM was recommended for patients with OAB and BPS/IC who previously had unsuccessful conservative and medical therapies and botulinum toxin injections. Success was defined as more than 50% improvement in clinical symptoms or voiding diary parameters in patients with OAB; more than 50% improvement in storage symptoms or subjective pain improvement or improvement after pain medications in patients with BPS/IC; more than 50% reduction in urethral catheterization rate in patients with IUR. We reviewed the success rates and complications.Results:Twenty-four patients underwent the first stage of SNM and 16 patients (66.6%) received permanent implantation. Ten patients were female (62.5%) and six were male (37.5%). The mean age was 36.9 years. Seven patients (43.7%) had OAB, three patients (18.7%) had BPS/IC, and six patients (37.5%) had IUR. After a mean follow-up of 42.3 months, the overall success rate was 87.5% for all indications. The success rate was 100%, 100%, and 66.7% for OAB, BPS/IC, and IUR, respectively. Four patients underwent surgical reintervention: two had their devices removed due to failure (50%), one had their implantable pulse generator (IPG) repositioned due to serious pain (25%), and one changed IPG due to malfunction (25%).Conclusion:SNM is a safe and effective minimally invasive therapy for patients with non-neurogenic urological disorders.